2019
DOI: 10.1111/odi.13049
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative circulating platelet, neutrophil, and lymphocyte counts predict survival in oral cancer

Abstract: Objective: Circulating immune-inflammatory cells have been increasingly recognized as robust prognostic biomarkers in cancer. Here, we sought to evaluate the prognostic values of preoperative peripheral platelet, neutrophil, lymphocyte quantitation in patients with primary oral squamous cell carcinoma (OSCC). Materials and methods:A total number of 309 patients with primary OSCC surgically treated at our institutions were retrospectively included. Detailed demographic, clinicopathological, laboratory, and foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
4
25
1
3
Order By: Relevance
“…Recent studies have shown that various pro-inflammatory mediators are associated with tumor progression at different stages of head and neck squamous cell carcinoma (HNSCC), and contribute to cancer cell proliferation, neovascularization, distant metastasis, and drug resistance. In previous studies, complex inflammation was demonstrated to play an essential role in the progression and metastasis of HNSCC (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that various pro-inflammatory mediators are associated with tumor progression at different stages of head and neck squamous cell carcinoma (HNSCC), and contribute to cancer cell proliferation, neovascularization, distant metastasis, and drug resistance. In previous studies, complex inflammation was demonstrated to play an essential role in the progression and metastasis of HNSCC (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…12,27,28 The important role of unresolved inflammation in HNSCC progression and metastasis is well established in previous studies. 12,17,27,28 Firstly, elevated blood neutrophil counts in an inflammatory microenvironment have been shown to contribute to tumor angiogenesis. It induces the resistance to antivascular endothelial growth factor (anti-VEGF) therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple inflammatory markers have been long since emerging as surrogate biomarkers and as prognostic indicators for patients with oral cavity/oropharyngeal carcinoma and other solid cancers, 14,15 such as neutrophil, lymphocyte, monocyte, platelet counts, either as individual values or ratios to each other. [17][18][19][20] As it is well known, platelet count (PLT) is critical in coagulation and inflammation. Moreover, activated platelets are linked to increased cancer risk through various mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that preoperative peripheral neutrophil and lymphocyte counts were correlated with survival in oral cancer. 12,13 But the prognostic value of inflammatory markers has not been fully elucidated in patients with advanced OSCC undergoing CRT. Thus, it is necessary to assess the available pretreatment parameters in order to develop a prognostic model for the prediction of survival outcomes in OSCC patients.…”
Section: Introductionmentioning
confidence: 99%